Blended Learning in Tertiary Accounting Education in the CEE Region – A Polish Perspective - Konrad Grabinski; Marcin Kedzior; Joanna Krasodomska (Journal of Accounting and Management Information Systems (JAMIS), 2015)
Nowadays, universities increasingly exploit the potential of the internet implementing blended learning as a key feature of modern education. The paper focuses on the quality, benefits and drawbacks of online academic accounting courses. On the basis of literature review and previously performed empirical studies we have developed four research hypotheses. In order to verify them, we have conducted a survey among students at Cracow University of Economics in Poland. The sample consists of 713 students who participated in blended learning courses in International Accounting, Bank Accounting and Controlling and Accounting Computer Systems. The results of the survey have shown that blended learning is positively perceived by students. Over half of them stated that e-classes did not differ from the traditional ones in terms of difficulty. The most important benefits of e-classes were: the possibility of learning at any place and time, saving time and lower costs of education. The most serious drawbacks included the impossibility to ask questions on a regular basis, the lack of direct contact with the teacher and the need for independent education organization. The regression analysis has provided evidence that students' attitude towards e-classes is the most important determinant of their satisfaction with the course after its completion.
Keywords: M49; 650; online courses; e-learning; blended learning; accounting education